2015
DOI: 10.1155/2015/616478
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Different Operating Systems for Femtosecond Lasers in Cataract Surgery

Abstract: The introduction of femtosecond lasers is potentially a major shift in the way we approach cataract surgery. The development of increasingly sophisticated intraocular lenses (IOLs), coupled with heightened patient expectation of high quality postsurgical visual outcomes, has generated the need for a more precise, highly reproducible and standardized method to carry out cataract operations. As femtosecond laser-assisted cataract surgery (FLACS) becomes more commonplace in surgical centers, further evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…Direct comparisons between platforms and cannulation devices have not been undertaken however but in this manuscript we have shown how a flat interface causes significant rise in comparison to a liquid one. A curved interface represents a compromise between distortion of the cornea and associated pressure rises and a full liquid interface 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Direct comparisons between platforms and cannulation devices have not been undertaken however but in this manuscript we have shown how a flat interface causes significant rise in comparison to a liquid one. A curved interface represents a compromise between distortion of the cornea and associated pressure rises and a full liquid interface 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The interface is fixated on the patient's eye using a suction ring (Nagy ; Wu et al. ). To maintain a sufficient connection between the patient's eye and the suction ring, an adequate amount of vacuum is needed (Donaldson et al.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the 150% setting has incrementally lower energy than for platforms operating in the microjoule range. 15 We cannot explain why the stretch ratio increased at 150% energy as intuitively as we might have expected this to reduce. The elastic recoil seen in the capsulotomy was consistent with our previous data and the behavior of porcine lenses.…”
Section: Figurementioning
confidence: 86%
“…15,35,37 We have previously evaluated the role of the Ziemer LDV Z8 nanojoule energy platform on lens capsulotomies, which had shown consistency and resistance to rupture with this system. 30 Increasing energy in the microjoule range may adversely affect capsulotomy strength and increase cell death in high-energy platforms (5-15 lJ), 23,31 but smaller increase in energy as a means of safely circumventing the effects of corneal edema with a low-energy laser (<100 nJ or 0.1 lJ) 15 has not been previously determined. Therefore, in this study we found that the consistency of circularity and lens elasticity was seen both in clear corneas and at increased laser energy-from a conventional recommended setting of 90% to 150%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation